The impact and transformation of education policy in China - Huang, Tiedan; Wiseman, Alexander W., 1968- (Bingley, U.K. : Emerald, 2011)
This volume of the International Perspectives on Education and Society series examines the transformation of education policy in China, with a special emphasis on transformations in the post-1978 period. While educational policy has experienced major shifts and reversals since the founding of the Peoples Republic of China in 1949, the late 1970s and the early1980s signalled a significant shift in Chinas openness and willingness to make widespread and rapid changes in education to meet the demands of an increasingly market-oriented economy. These educational policy changes are inextricably linked to Chinas increasing interest and participation in the global community abroad and the social-economic transformation and somewhat loosened political environment at home. With the special emphasis on policy change and its subsequent impact on different aspects of education at various levels of educational institutions, particularly in areas of educational financing and curriculum reform, this volume attempts to bridge the dichotomy between critics and advocates of Chinese educational transformations, recognize the importance and impact that educational policy in China has not only on one of the largest national populations in the world, but also on other (and often competing) countrys systems and provide relevant scholarship to inform policy and practice.
The development of comparative education research on Chinese educational policy reform : an introduction / Alexander W. Wiseman, Tiedan Huang -- Moving toward decentralization? : changing education governance in China after 1985 / Tingting Qi -- Interprovincial and regional inequity in the financing of compulsory education in China / Xin Gong, Mun C. Tsang -- Wearing new shoes to walk the old road : the negotiation of opposing imperatives in high school new curriculum classes in China / Tanja Sargent, Mingyu Chen, Yi-Jung Wu, Chentong Chen -- China's new millennium curriculum reform in mathematics and its impact on classroom teaching and learning / Yujing Ni, Qiong Li, Xiaoqing Li, Jun Zou -- The landscape of principal leadership development in mainland China : an analysis of Chinese and English research / Tiedan Huang, Alexander W. Wiseman -- Defining school effectiveness in the reform for quality-oriented education / Xiu Chen Cravens, Hongqi Chu, Qian Zhao -- The 'gap' between policy intent and policy effect : an exploration of the interpretations of school principals in China / Haiyan Qian, Allan Walker -- Reforming the college entrance examination : epicenter of tension, change, and resistance / Heidi Ross, Yimin Wang -- Importance of home environment for children's schooling : from the teacher's perspective / Yuping Zhang -- Educational barriers for migrant children in China : a mixed-method analysis focused on ethnic minorities / Henan Cheng -- Education technology as a catalyst for education development in China : a policy perspective / Yumin Xiao, Ellen B. Meier -- Quality assurance in undergraduate education : transformation of higher education policy in China / Kathryn Mohrman, Yingjie Wang, Xu Li -- The role of private higher education in the Chinese higher education system / You Guo Jiang.
Print version record
Keywords: Education -- Educational Policy & Reform -- General; Education -- General; Political Science -- Public Affairs & Administration; Educational strategies & policy; Organization & management of education; Education and state -- Asia; Education -- Asia